2015
DOI: 10.1002/hbm.22760
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin selectively facilitates learning with social feedback and increases activity and functional connectivity in emotional memory and reward processing regions

Abstract: In male Caucasian subjects, learning is facilitated by receipt of social compared with non-social feedback, and the neuropeptide oxytocin (OXT) facilitates this effect. In this study, we have first shown a cultural difference in that male Chinese subjects actually perform significantly worse in the same reinforcement associated learning task with social (emotional faces) compared with non-social feedback. Nevertheless, in two independent double-blind placebo (PLC) controlled between-subject design experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
78
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 66 publications
(94 reference statements)
12
78
3
1
Order By: Relevance
“…Kohls et al (2013), for instance, found activations in the putamen and thalamus when social approval was anticipated, whereas Smith et al (2010) reported activations in these two brain areas when research participants felt rewarded after looking at attractive faces. Parallel to our findings, Hu et al (2015) recently showed that activations in both the putamen and the thalamus occurred when individuals were rewarded by a smile from another person. Additionally, Pfeiffer et al (2014) reported that putamen and thalamus activations were found when participants interacted with another person in an experiment, while these activations were not found when participants interacted with a computer.…”
Section: Management-related Rewards and Their Neurophysiological Actisupporting
confidence: 90%
“…Kohls et al (2013), for instance, found activations in the putamen and thalamus when social approval was anticipated, whereas Smith et al (2010) reported activations in these two brain areas when research participants felt rewarded after looking at attractive faces. Parallel to our findings, Hu et al (2015) recently showed that activations in both the putamen and the thalamus occurred when individuals were rewarded by a smile from another person. Additionally, Pfeiffer et al (2014) reported that putamen and thalamus activations were found when participants interacted with another person in an experiment, while these activations were not found when participants interacted with a computer.…”
Section: Management-related Rewards and Their Neurophysiological Actisupporting
confidence: 90%
“…These analyses reveal an increase in correlated Fos expression across PBN nuclei in aCSF-treated subjects relative to both unexposed controls and OTA-treated subjects, consistent with the hypothesis that central OTR signaling during sociosexual interaction and mating with a female enhances functional connectivity across the PBN in male prairie voles. These data are interesting in light of recent human fMRI studies showing that intranasal OT administration increases functional connectivity across a variety of striatal and limbic nuclei during various social contexts (Fan et al, 2015; Gorka et al, 2015; Hu et al, 2015; Riem et al, 2012); however, studies using intranasal OT should be interpreted with caution (Walum et al, 2015). …”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported OXT effects on DMN regions associated with self‐processing, including increased activation in both the ACC and precuneus during self‐processing of disgust and in the insula for both self and other processing [Scheele et al, ]. Other studies have also reported OXT effects on functional connectivity involving the insula [Hu et al, ' Striepens et al, ] and mPFC [Sripada et al, ], although this has not been investigated in the context of self‐processing. In another event related potential study, OXT was found to decrease the differential amplitudes of a frontocentral positivity at 220 to 280 ms (P200) in the area of the mPFC and ACC during self‐ vs. valence‐judgments (self‐referential processing) [Liu et al, ].…”
Section: Introductionmentioning
confidence: 99%